Getting connected with facebook messenger: exploring meaningful interactions through online chats in the ESL context - Samani, Ebrahim; Noordin, Nooreen (Imam Khomeini International University, 2020)
The number of online users has unprecedentedly increased in recent years. The rapid advancement of technology has seen the growth of social media usage and this has made a huge impact on today’s educational system. However, to what extent has social media played an important role in the teaching and learning process particularly in the English Language Teaching (ELT) is still unclear. This is due to the fact that in most cases, social media is used for the purpose of entertainment and personal usage. The current study attempted to explore the nature of communications via social media and how they can be used in improving students’ language skills. Participants in this study consisted of fifteen undergraduate students who were into their second year of the TESL program. They were involved in completing a grammatical task through the use of Facebook Messenger, an online platform where they engaged in chat activities. The discussion which was moderated by the researcher lasted 45 minutes for each session and five sessions were conducted where sentence combining activities were also done using the Facebook Messenger. Results obtained from the discourse analysis done which examined the participants’ accounts of their experiences, as well as the pedagogical features of the online platform, clearly show that this platform can be used as a pedagogical tool in improving language skills.